Formation of oxygen vacancy at surfaces of ZnO by trimethylaluminum - Eom, Hyobin; Bae, Woojin; Sung, Ju Young; Choi, Ji Hyeon; Dae, Kyun Seong; Jang, Jae Hyuck; Park, Tae Joo; Lee, Sang Woon; Shong, Bonggeun (APL Materials, 2024)
The two-dimensional electron gas (2DEG) is a group of electrons that can move freely in horizontal dimensions but are confined in the third direction. It has been reported that atomic layer deposition (ALD) of Al2O3 on various reducible n-type oxides can lead to the formation of 2DEG at the heterojunction interfaces, among which ZnO is known to provide promising properties. In this study, we have performed a theoretical analysis using density functional theory calculations combined with experimental investigations to elucidate the surface reactions of Al2O3 ALD on low-index nonpolar ZnO surfaces, specifically focusing on the formation of oxygen vacancies (VO). The trimethylaluminum precursor was observed to undergo sequential dissociation of CH3 ligands, leading to the removal of surface oxygen of ZnO in the form of dimethyl ether. In addition, by examining the electronic structure after the removal of oxygen, the localization of the charge density at the surface was confirmed. Experimentally, the carrier density of the 2DEG at the Al2O3/ZnO interface showed a strong dependence on the ALD process temperature of Al2O3, confirming the endothermic nature of the formation of the 2DEG. By examining the characteristics of the 2DEG induced by VO, insights into the fundamental comprehension of oxide-based 2DEG systems are provided.
Keywords: Atomic-layer deposition; Density-functional theory calculations; Experimental investigations; Heterojunction interfaces; Low index; Non-polar; Property; Trimethylaluminum; Two-dimensional electron gases (2DEG); ZnO surface